Дослідження інституційного середовища управління людськими ресурсами в Україні - Лаптєв, В.І. (Стратегія і механізми регулювання промислового розвитку, 2016)
Стаття присвячена актуальному питання управління найбільш цінним ресурсом сьогодення - людиною. Проаналізовано сутність людських ресурсів, визначено проблему врахування інституційного середовища при управлінні людськими ресурсами. Запропоновано систематизацію інститутів, які здійснюють координацію управління людськими ресурсами, а також розкрито сутність впливу кожного з них. Статья посвящена актуальному вопросу управления наиболее ценным ресурсом сегодняшнего дня - человеком. Проведен анализ сущности человеческих ресурсов, определена проблема учета институциональной среды при управлении человеческими ресурсами. Предложена систематизация институтов, осуществляющих координацию управления человеческими ресурсами, а также раскрыта сущность влияния каждого из них. This article is devoted to the topical problem of managing the most valuable resource of today - a human being, since human resources are the most effective because they only accumulate their potential, developing knowledge and experience that help the enterprise to make profit and form competitive advantages. The work analyzes the essence of human resources, the problem of accounting for the institutional environment in the management of human resources. The systematization of institutions providing coordination of human resources management is proposed, as well as disclosure of the essence of the influence of each of them. The theoretical value in this article is a classification that takes into account a combination of two classification groups, united by the level of distribution and the distribution object. The first takes into account the macro, meso- and microlevel, while the second illustrates three types of institutions: state, non-state and informal. State institutions are represented by the Cabinet of Ministers and other executive bodies that coordinate various areas of social and labor relations. Non-governmental institutions are represented by trade unions, recruitment agencies, outsourcing companies and non-governmental organizations, which provides protection for participants in labor relations. The list of informal institutions consists of religion, social behavior, traditions, the shadow labor market.